Language Teaching during a Pandemic: A Case Study of Zoom Use by a Secondary ESL Teacher in Hong Kong. (April 2023) - Cheung, Anisa
This article reports a case study of an English as a Second Language (ESL) teacher in Hong Kong who conducted lessons via Zoom during the COVID-19 pandemic. The study focused on the factors influencing her technology integration in synchronous online teaching mode. Using data from classroom recordings, stimulated-recall and semi-structured interviews, this study uncovered how Zoom functioned as a substitute for face-to-face lessons. The findings revealed that although there were fewer interactions between the teacher and her students, teaching in synchronous online mode provided the teacher with opportunities to utilize certain online features to augment methods of checking student understanding. The study identified the teacher's pedagogical beliefs, the context and professional development as factors that influenced the level of technology integration in her Zoom classes. The study concludes that embracing process-oriented pedagogies may be necessary for a higher level of technology integration among ESL teachers who have adequate professional development opportunities and school support.